Explaining the labour market outcomes of first, second and third generation immigrants in Canada - Jiong Tu (Institute for the Study of Labor (IZA), 2010)
This paper examines the effectiveness of Canadian immigration policy by analyzing the differences in the returns to education between first, second and third generation immigrant men. Regression results indicate that the second generation with high school education and lower do not earn significantly less than the equally educated third generation. However, the second generation with at least postsecondary education experience a wage deficit to the third generation. I explain the well-educated second generation's difficulty in translating their intellectual ability into productivity by their ethnic and linguistic distance from the Canadian mainstream, and by a negative city-specific effect. Regression results using sub-samples categorized by subsequently interacting educational attainments with ethnicity, mother tongue and city of residence support these explanations. I then suggest that assimilation policies targeting the well-educated first and second generation immigrants be designed to promote the acceptance of their human capital by the Canadian labour market.
urn:nbn:de:101:1-201010132836
Keywords: F22; J15; J31; J62; 330; immigrant; second generation; wages; education; ethnicity; Canada